Science Journalists: The Myth Is as Good as a Mile - Joseph J. Marks (Journal of Applied Communications, 1981)
A paper presented at Mackinac Island, Michigan, July 15, 1981, "…to keep science journalism types from being so…serious that they can't communicate with anyone but other scientists or each other."